2008
DOI: 10.1080/19396360701883266
|View full text |Cite
|
Sign up to set email alerts
|

Absence of theH2AXMutations in Idiopathic Infertile Men with Spermatogenic Impairment

Abstract: H2AX is a histone H2A variant and one of the evolutionarily conserved fertility factors involved in DNA repair to maintain the genomic integrity and ensure the proper meiotic process. Male H2ax mutant mice are infertile and display defective meiosis. To investigate the possible association of variations of the H2AX gene with spermatogenic impairment in humans, mutation screening of the entire coding region of this gene was carried out in 302 patients with azoospermia or severe oligospermia along with 198 normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…However, in our previous study in infertile men, we did not find any mutations or genetic risk factors of H2AX [24]. On the other hand, male mice with null Tssk6 were infertile.…”
Section: Discussioncontrasting
confidence: 62%
“…However, in our previous study in infertile men, we did not find any mutations or genetic risk factors of H2AX [24]. On the other hand, male mice with null Tssk6 were infertile.…”
Section: Discussioncontrasting
confidence: 62%
“…3,49 Several other studies have investigated genes including SYCP3, SPO11, FKBP6, BOULE, H2AX and REC8, but have failed to identify any disease-causing mutations. 3,[50][51][52][53][54][55][56][57] The initiation of meiotic recombination is regulated in a large part by the protein SPO11. The SPO11 protein is a type II topoisomerase required for DSB formation in the leptotene stage.…”
Section: Meiotic Recombinationmentioning
confidence: 99%
“…Indeed, although some infertility studies have identified disease-causing mutations, [4][5][6] others have failed to identify any causal mutations, possibly due to the heterogeneous etiology of infertility. [7][8][9][10][11][12][13][14] Even when samples are appropriately collected from patients with a meiotic defect, this complicated biological process in prophase I is mediated by numerous meiotic genes responsible for homologous recombination, synapsis or sister chromatid cohesion. Indeed, even in yeast it is estimated that hundreds of genes may be involved in the meiotic process.…”
Section: Introductionmentioning
confidence: 99%